Studying and Analyzing Anti-Roll Tanks Parameters Effects on Reducing Marine Vessels Rolling - بربهان ميشيل; ميهوب غيث (Latakia University Journal -Engineering Sciences Series, 2021)
The research aims to find an algorithm to determine the parameters of the appropriate damping tanks, in order to provide the largest possible damping moment, taking into account not to negatively affect the initial ship’s stability. The research depends on determining the equations of the motion of the ship’s vibration, and the equation of movement of the fluid in the damping tank. To choose the optimal tank dimensions, a preliminary design conditions were set, and a program using Visual Basic.net as a programming language was developed. The dimensions of tank were inserted into the equations of motion. These equations were solved using Matlab program to determine the effect of the reservoir parameters and the frequency of the incoming waves on the ship’s transverse oscillation.